PrEP preferences and early acceptability of injectable cabotegravir among pregnant and lactating people in Cape Town, South Africa: findings from the PrEPared to Choose study - Nafisa Wara; Carey Pike; Elzette Rousseau; Pippa Macdonald; Pakama Mapukata; Bryan Leonard; Keitumetse Lebelo; Risa Hoffman; Catherine Orrell; Linda‐Gail Bekker; Dvora Joseph Davey (Journal of the International AIDS Society, 2025)
Abstract Introduction Providing pregnant and lactating people (PLP) with choice in HIV pre‐exposure prophylaxis (PrEP) methods, including long‐acting injectable cabotegravir (CAB‐LA), may mitigate barriers to effective PrEP use. We evaluated PrEP preferences and acceptability among PLP offered CAB‐LA versus oral PrEP in South Africa. Methods The PrEPared to Choose study in Cape Town, South Africa, enrolled young people ages 15–29 at one public clinic and one community‐based mobile clinic. Using informed choice counselling, participants were offered oral PrEP or CAB‐LA, with the option to switch methods at follow‐up visits over 18 months. We report baseline CAB‐LA and oral PrEP initiations among PLP in the study, acceptability of their initial choice within 3 months of enrolment and theoretical preferences regarding PrEP methods that may become available to PLP. We report descriptive statistics and use Chi‐square and Fisher's exact to compare responses by initiated PrEP method and pregnancy status. Results From February to August 2024, we enrolled 58 PLP (n = 30 pregnant, n = 28 breastfeeding). Median age 23 years (IQR 19.5−26). Of 30 pregnant participants, 23 (77%) initiated CAB‐LA and seven (23%) oral PrEP; among 28 breastfeeding participants, 25 (89%) initiated CAB‐LA and three (11%) oral PrEP. Of enrolled PLP, 36 (62%, n = 13 pregnant, n = 23 breastfeeding) completed the acceptability survey. Of these, 83% (n = 12/13 pregnant, n = 20/23 breastfeeding) chose and received CAB‐LA, and the remaining (n = 4) chose and received oral PrEP. PLP who received CAB‐LA reported liking its ease of use (69%; n = 22/32) and long‐acting protection (44%; n = 14/32). Half of CAB‐LA users disliked side effects (e.g. injection site pain), although 41% of PLP (n = 13/32) described no CAB‐LA dislikes. Almost all (97%; n = 31/32) PLP currently using CAB‐LA were interested in continuing CAB‐LA, and all PLP using oral PrEP reported interest in trying CAB‐LA in the future. Eighty‐six percent of surveyed PLP (n = 31/36) did not want to try the dapivirine vaginal ring. Conclusions PLP in South Africa had a strong preference for CAB‐LA over oral PrEP, and CAB‐LA was found to be highly acceptable. Further research is needed to evaluate the effect of offering choice of PrEP methods, including CAB‐LA, on PrEP continuation among PLP.